The Concept of Brotherhood of Hope in QS Al-Hujurat Verses 11-13 Perspective of the Interpretation of Al-Misbah and Al-Azhar - Subli Ibrahim; Aris Fauzan; Halim Purnomo (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study aims to describe the concept of brotherhood of hope in QS Al-Hujurat verses 11-13, to describe the concept of brotherhood of hope in the Qur'an according to Tafsir al-Misbah and Tafsir al-Azhar in QS Al-Hujurat verses 11-13, describe the implications of brotherhood of hope in QS Al-Hujurat verses 11-13. The method used is library research with a comparative approach and the theory of meaning and understanding between Tafsir al-Misbah and Tafsir al-Azhar in QS al-Hujurat: 11-13. The data analysis process with data collection, data reduction and conclusions. This study explains that the siblinghood of hope is formed from several types of relationships, namely: traditional full sibling individuals who have the same biological parents, half sibling individuals who have one parent in common, step sibling individuals who do not have the same biological parents but have a relationship resulting from marriage between parents, adoptive sibling individuals who are legally adopted by a family, and fictive sibling individuals who have been related siblings. The brotherhood of hope according to M. Quraish Shihab is a brotherhood that is not limited to relationships between believers but across religions and social groups. According to Buya Hamka, the relationship is based on ideological similarities and one descent.